Cortico-subthalamic Coherence in a Patient With Dystonia Induced by Chorea-Acanthocytosis: A Case Report - Cao, Chunyan; Huang, Peng; Wang, Tao; Zhan, Shikun; Liu, Wei; Pan, Yixin; Wu, Yiwen; Li, Hongxia; Sun, Bomin; Li, Dianyou; Litvak, Vladimir (Frontiers in Human Neuroscience, 2019)
The subthalamic nucleus (STN) is a common target for Deep Brain Stimulation treatment in Parkinson’s Disease (PD) but much less frequently targeted for other disorders. Here we report the results of simultaneous local field potential recordings and magnetoencephalography in a single patient who was implanted bilaterally in the STN for the treatment of dystonia induced by chorea-acanthocytosis. Consistent with the previous results in PD, the dystonia patient showed significant subthalamo-cortical coherence in the high beta band (28-35Hz) on both sides localised to the mesial sensorimotor areas. In addition, on the right side significant coherence was found in the theta-alpha band (4-12Hz) that localised to the medial prefrontal cortex with the peak in the anterior cingulate gyrus. Comparison of STN power spectra with a previously reported PD cohort showed increased power in the theta and alpha bands and decreased power in the low beta band in dystonia which is consistent with most of the previous studies. The present report extends the range of disorders for which cortico-subthalamic oscillatory connectivity has been characterised. Our results strengthen the evidence that at least some of the subthalamo-cortical oscillatory coherent networks are a feature of the healthy brain, although we do not rule out that coherence magnitude could be affected by disease.